Intraoperative visualisation of pancreatic leakage (ViP): study protocol for an IDEAL stage I post market clinical study - Pausch, Thomas; Holze, Magdalena; Gesslein, Bodil; Rossion, Inga; Eisenhart Rothe, Franziska von; Wagner, Martin; Sander, Anja; Tenckhoff, Solveig; Bartel, Marc; Larmann, Jan; Probst, Pascal; Pianka, Frank; et al. (BMJ open, 2022)
Introduction Pancreatic resections are an important field of surgery worldwide to treat a variety of benign and malignant diseases. Postoperative pancreatic fistula (POPF) remains a frequent and critical complication after partial pancreatectomy and affects up to 50% of patients. POPF increases mortality, prolongs the postoperative hospital stay and is associated with a significant economic burden. Despite various scientific approaches and clinical strategies, it has not yet been possible to develop an effective preventive tool. The SmartPAN indicator is the first surgery-ready medical device for direct visualisation of pancreatic leakage already during the operation. Applied to the surface of pancreatic tissue, it detects sites of biochemical leak via colour reaction, thereby guiding effective closure and potentially mitigating POPF development. - Methods and analysis The ViP trial is a prospective single-arm, single-centre first in human study to collect data on usability and confirm safety of SmartPAN. A total of 35 patients with planned partial pancreatectomy will be included in the trial with a follow-up of 30 days after the index surgery. Usability endpoints such as adherence to protocol and evaluation by the operating surgeon as well as safety parameters including major intraoperative and postoperative complications, especially POPF development, will be analysed. - Ethics and dissemination Following the IDEAL-D (Idea, Development, Exploration, Assessment, and Long term study of Device development and surgical innovation) framework of medical device development preclinical in vitro, porcine in vivo, and human ex vivo studies have proven feasibility, efficacy and safety of SmartPAN. After market approval, the ViP trial is the IDEAL Stage I trial to investigate SmartPAN in a clinical setting. The study has been approved by the local ethics committee as the device is used exclusively within its intended purpose. Results will be published in a peer-reviewed journal. The study will provide a basis for a future randomised controlled interventional trial to confirm clinical efficacy of SmartPAN. - Trial registration number German Clinical Trial Register DRKS00027559, registered on 4 March 2022.
Gesehen am 30.01.2023